Young adults’ views on the mechanisms underpinning the impact of pets on symptoms of anxiety and depression - Hawkins, Roxanne D.; Kuo, Chih-Hsin; Robinson, Charlotte (Frontiers in Psychiatry, 2024)
Emerging adulthood is considered a peak age for the onset of mental health difficulties with approximately 75% of mental health disorders being diagnosed during this developmental period. Companion animals confer both risk and benefits to mental health yet the potential underpinning mechanisms which explain such impacts are not fully understood. This study aimed to gather an in-depth understanding of young adults’ lived experience of how their companion dogs and cats may impact their mental health symptoms and the perceived mechanisms which explain their effects. Semi-structured interviews were carried out with 16 young adults aged 18-26 years, from the United Kingdom, who either had a companion dog, cat, or both. All participants had difficulties with anxiety and or depression, and 12 had received a formal diagnosis of an affective disorder. Five overarching themes and one subtheme were identified through reflexive thematic analysis using an inductive approach: Theme 1: Pet impact on generalized anxiety and panic, Subtheme 1A: Pet impact on social anxiety and loneliness; Theme 2: Pet impact on low mood, depression, and stress; Theme 3: Pet impact on severe mental health and suicide prevention; Theme 4: Staying well; Theme 5: Positive outlook and successful futures. Several perceived mechanisms underpinning the impacts of pets for mental health were also identified. These findings have relevance for the development and evaluation of mental health interventions and treatment protocols aimed at young adults with mental health difficulties, where companion animals may prove to be effective for symptom management and improvements in positive wellbeing.